The impact of regional specialization on wages of women and men in ICT sector in Poland in 2012-2016 - Agata Gomółka (Economic and Environmental Studies (E&ES), 2018)
The aim of the presented study is to demonstrate the impact of regional specialization on total remuneration, disaggregated by gender in the ICT sector in Poland in 2012-2016. The first part of the article presents the general characteristics of the Polish ICT industry and shows (using the location quotient) regions in Poland that could be treated as areas of high concentration of specialization in this field; in the second part, the wages of men and women in the ICT sector are compared for the years 2012-2016; the third part presents the results of a statistical analysis of the impact of regional specialization on wages disaggregated by gender. The study ends with a summary and conclusions. The estimation of the parameters of the equations used in the analysis shows that the values of the location quotient (as a measure of regional specialization) largely explains the variation in total wages and the gender distribution with the following relationships - the greater the regional specialization, the higher the average wage and vice versa. However, the location quotient values do not explain the differentiation of the gender pay gap and it is not possible, on the basis of the analysed data, to claim any dependencies between regional specialization and the gender pay gap existing in a given voivodeship.
Keywords: J31; O14; 330; regional specialization; gender pay gap; ICT sector